The Effect of Mocaf Flour and Yellow Pumpkin Flour (Cucurbita Moschata) Proportion on the Acceptability and Physicochemical Quality of Wet MI - Ni’mah, Isna Khairun; Syainah, Ermina; Yanti, Rusmini; Aprianti; Nurhamidi; Farhat, Yasir (International Journal of Public Health Excellence (IJPHE), 2024)
Overcoming dependence on wheat flour as raw material, researchers want to develop a wet noodle product by using mocaf flour to substitute wheat flour and adding pumpkin flour to increase the nutritional value of wet noodles, namely potassium minerals as an alternative main food that can help lower blood pressure in hypertension sufferers.To determine the effect of the proportion of mocaf flour and pumpkin flour on the physicochemical quality of wet noodles. This type of research uses an experimental study design with a Completely Randomized Design (CRD). The comparison of the proportions of mocaf flour and pumpkin flour is P0 (100g : 0g), P1 (95g : 5g), P2 (90g :10g), P3 (85 g :15g), P4 (80g :20g). Physical quality and chemical quality test data were analyzed using the Independent T-test. The research results show that the percent water absorption capacity; percent elongation; potassium levels; and sodium levels, namely P0 (58.5% ; 19.8% ; 16.5mg/100 g; 5.64 mg/100g), P2 (70.3% ; 8.8% ; 55.95 mg/100g ; 5.55 mg/100g). The best treatment P2 does not meet the adult RDA percentage and cannot be classified as high in potassium. Wet noodle products cannot yet be used as an alternative to foods high in potassium for preventing hypertension.